PERAN IBU DALAM MENJALANKAN POLA ASUH ANAK DI RW 29 KELURAHAN SIMPANG BARU KECAMATAN TAMPAN (STUDI KASUS KELUARGA SINGLE PARENT) - Nora Hawita; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The purpose of this study was to determine the role of a mother as a single parent in maintaining socio-economic impact of the family and the child's independence. The method used in this research is descriptive qualitative, where the informant is taken that the mother has been a single parent in RW 29. To determine informants pusposive researchers used a technique of sampling and data collection techniques by observation and interviews. Being a single parent for a mother is not easy because of the challenges that will be undertaken, namely a dual role in running the upbringing of children. In order for the functioning of the family, where the mother's role in parenting will affect the independence of a child. From observations and interviews can be seen that being a single parent is not easy for a mother and have challenges in their parenting to children is raising and educating children and fulfill the needs of the family, where the fifth informant had the same problem, namely the problem of educating children alone.Keywords: Single Parent, Dual Role, Parenting Children